Beginning Visual Web Programming in VB .NET - Cazzulino, Daniel (Apress, 2012)
The introduction of .NET has blurred the lines between previously distinct programming disciplines, and it has done so to great effect for developers. With so much functionality encapsulated by the .NET Framework class library, some diverse tasks have gained a common programming interface. One area in which this change is particularly striking is that of web development. Before .NET, web application programming “the Microsoft way” was all about ASP. At the time, ASP was new, accessible, and exciting. But it was also script-based and inefficient. It led to serious maintainability problems, and the IDEs were disjointed. Microsoft has channeled the lessons it learned from ASP into its .NET Framework. Now, with ASP.NET (the .NET web development technology), you can create efficient, interactive Internet applications using the same languages that you use for Windows desktop applications. In Visual Studio .NET (VS .NET), Microsoft has taken this idea even further; not only does the code look similar, but the GUI looks similar, too. Visual Basic .NET’s (VB. NET’s) familiar form-based interface is used for development of web applications, as well as for desktop programs. If you want to, you can create a web application without ever seeing a line of HTML code, and you can take advantage of all the facilities for testing and debugging that VS .NET provides to programmers of all disciplines. The structure of class libraries in the .NET Framework is such that the methodology you use is the same, regardless of whether you’re developing desktop applications or web applications. ASP.NET is really just a series of classes in the .NET Framework, just like the Windows Forms classes. From this perspective, the move from desktop application development to web development shouldn’t be too much of a leap.